Pengaruh Machiavellian Dan Love Of Money Terhadap Persepsi Etika Penggelapan Pajak Dengan Religiusitas Sebagai Variabel Moderasi: - Muharsa Farhan; Herlina Helmy; Mayar Afriyenti (Jurnal Eksplorasi Akuntansi, 2019)
This study aims to determine: (1) The influence of machivellian on the ethics perception of tax evasion, (2) The influence of love of money on the ethics perception of tax evasion, (3) Religiosity moderates relations between machiavellian on the ethics perception of tax evasion, (4) Religiosity moderates relations between love of money on the ethics perception of tax evasion, The population in this study is taxpayers in Padang city. The sample is determined based on the non-probability sampling method. The data used in this study are primary data. This study used a questionnaire instrument of 400 respondents. The method of analysis is done using MRA (Moderated Regression Analysis).The results showed that machivellian had not significant effect on the ethics perception of tax evasion, love of money had a significant negative effect on the ethics perception of tax evasion, religiosity had not moderate relation between machivellian on the ethics perception of tax evasion, religiosity strengthens relation between love of money influence on the ethics perception of tax evasion